2009
DOI: 10.1603/033.046.0331
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies of Japanese Encephalitis Virus Infection in Vector Mosquitoes in Kurnool District, Andhra Pradesh, South India

Abstract: A 4-yr (2002-2006) entomological study was carried out in Kurnool district, Andhra Pradesh state, south India, to identify the mosquito vectors of Japanese encephalitis virus (family Flaviviridae, genus Flavivirus, JEV). In total, 37,139 female mosquitoes belonging five genera and 18 species resting on vegetation were collected in villages and periurban areas at dusk. Mosquito species composition and pattern of JEV infection in mosquitoes varied in periurban and rural areas. In periurban area, Culex gelidus Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…However, in both Sri Lanka, and India this pattern appears to have changed with the disease now spreading to rural areas as well 25 . Although vector densities are generally much higher in urban areas when compared to rural areas, vector densities in rural areas are now seen to be quite high 10,26 . Therefore, the potential 'threat' of major dengue outbreaks in rural areas is present.…”
Section: Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both Sri Lanka, and India this pattern appears to have changed with the disease now spreading to rural areas as well 25 . Although vector densities are generally much higher in urban areas when compared to rural areas, vector densities in rural areas are now seen to be quite high 10,26 . Therefore, the potential 'threat' of major dengue outbreaks in rural areas is present.…”
Section: Future Trendsmentioning
confidence: 99%
“…The rise in the incidence of dengue infections in the rural areas further adds to this threat 9,10 . Therefore, unless vector densities are reduced, dengue infections may overtake other infectious diseases as the number one killer in many countries in South Asia.…”
Section: Dengue Viral Infectionsmentioning
confidence: 99%
“…The blood samples were collected from the school children (6 to 10 years old) through finger prick method. The sera of school children were examined by haemagglutination inhibition (HI) test following protocol of Clarke and Casals (Arunachalam et al, 2009) for identifying the flavivirus antibodies (JE/West Nile/Dengue).…”
Section: Epidemiological Surveymentioning
confidence: 99%
“…Mosquitoes were sampled from identified villages at bimonthly Mutheneni et al 53 intervals during 2001 to 2006 and identified to species level (Arunachalam et al, 2009 …”
Section: Mosquito Collectionmentioning
confidence: 99%
See 1 more Smart Citation